Real Metal-Free C–H Arylation of (Hetero)arenes: The Radical Way - Bellina, Fabio (Synthesis, 2021)
Synthetic methodologies involving the formation of carbon–carbon bonds from carbon–hydrogen bonds are of significant synthetic interest, both for efficiency in terms of atom economy and for their undeniable usefulness in late-stage functionalization approaches. Combining these aspects with being metal-free, the radical C–H intermolecular arylation procedures covered by this review represent both powerful and green methods for the synthesis of (hetero)biaryl systems.1 Introduction2 Arylation with Arenediazonium Salts and Related Derivatives2.1 Ascorbic Acid as the Reductant2.2 Hydrazines as Reductants2.3 Gallic Acid as the Reductant2.4. Polyanilines as Reductants2.5 Chlorpromazine Hydrochloride as the Reductant2.6 Phenalenyl-Based Radicals as Reductants2.7 Electrolytic Reduction of Diazonium Salts2.8 Visible-Light-Mediated Arylation3 Arylation with Arylhydrazines: Generation of Aryl Radicals Using an Oxidant4 Arylation with Diaryliodonium Salts5 Arylation with Aryl Halides6 Conclusions
Keywords: metal-free reactions; C–H arylation; biaryls; radical reactions; photochemical reactions; (hetero)arenes; electron-transfer; mechanism